2008
DOI: 10.1177/0363546508314408
|View full text |Cite
|
Sign up to set email alerts
|

Section Modulus is the Optimum Geometric Predictor for Stress Fractures and Medial Tibial Stress Syndrome in both Male and Female Athletes

Abstract: The results show that in men, the cross-sectional area and the section modulus are the key parameters in the tibia to distinguish exercise and injury status, whereas for women, it is the section modulus only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
55
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 40 publications
9
55
2
1
Order By: Relevance
“…Comparable with a previous study conducted by Sharma, et al [2,3], the initial pass out rate was observed to vary between the regiments: Gurkha (98.76%), 53.78% for Guards and 64.47% for Line regiments. However, the initial pass out rate for the Parachute regiment was significantly lower (38.63%) than the other training regiments but observed to be slightly higher than previously published data for this regiment (35%) [35,36] and 38% [2,3]. These findings suggest a mismatch between the capacity of the musculoskeletal system and the demands of training.…”
Section: Training Outcome/attrition Ratecontrasting
confidence: 58%
“…Comparable with a previous study conducted by Sharma, et al [2,3], the initial pass out rate was observed to vary between the regiments: Gurkha (98.76%), 53.78% for Guards and 64.47% for Line regiments. However, the initial pass out rate for the Parachute regiment was significantly lower (38.63%) than the other training regiments but observed to be slightly higher than previously published data for this regiment (35%) [35,36] and 38% [2,3]. These findings suggest a mismatch between the capacity of the musculoskeletal system and the demands of training.…”
Section: Training Outcome/attrition Ratecontrasting
confidence: 58%
“…In the second and third experiments, the strain gauges were bonded to the tibia in predetermined locations using M-Bond 200 cement. Although the positions chosen were somewhat arbitrary as the aim was to validate the FE model in different locations, the magnitude of the stresses in the areas where TSFs [2,4,8,11,12] and Medial Tibial Stress Syndrome [2,13] are sustained were of interest; hence the gauges were attached to those sites.…”
Section: Rabbit Tibial Experimentsmentioning
confidence: 99%
“…To find the optimum number of data points required around a cross-section, convergence tests were performed using a Fortran program, where a number of cross-sectional properties were computed while varying the number of perimeter points. More details on these tests can be found in previous publications [2,14] . The third co-ordinate was based on the CT scan position along the longitudinal axis.…”
Section: Development Of the Tibial Fe Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In male military cohorts, parameters which have been associated with tibial SFs include a narrow mediolateral (ML) width at the narrowest tibial cross-section (Giladi et al, 1991;Giladi et al, 1987) and small diaphyseal dimensions relative to body weight (Beck et al, 1996). In both male military cohorts and male athletes, a low cortical bone cross-sectional area (Beck et al, 1996;Crossley et al, 1999;Franklyn et al, 2008), small second moments of area (Milgrom et al, 1989;Franklyn et al, 2008) and a small section modulus (Beck et al, 1996;Franklyn et al, 2008) have been associated with increased tibial SF risk. A major limitation with many of these studies is that only basic cross-sectional dimensions have been measured from the images, and when they are then used to calculate parameters such as the cross-sectional area, introduce significant error for an irregularly shaped object such as a tibial section.…”
Section: Tibial Cortical Bone Parametersmentioning
confidence: 99%